Decreasing incidence of ruptured abdominal aortic aneurysm already before start of screening. - Otterhag, Sofia Nessvi; Gottsäter, Anders; Lindblad, Bengt; Acosta, Stefan ; 0000-0002-3225-0798 (BMC Cardiovascular Disorders, 2016)
BACKGROUND: The aim of this study was to evaluate whether screening for abdominal aortic aneurysm (AAA) has led to a decrease in ruptured AAA (rAAA) incidence. METHOD: The Malmö population was evaluated regarding the incidence of rAAA and elective AAA surgery 4 years before and after start of AAA-screening in 2010. Data from 1971 to 1986 (J Vasc Surg 18:74-80, 1993) and 2000-2004 (J Vasc Surg 44:237-43, 2006), enabled analysis of trends over time. RESULTS: Analysis of time-periods 1971-1986, 2000-2004, 2006-2010 and 2010-2014 showed an incidence of rAAA of 5.6 (4.9-6.3), 10.6 (8.9-12.4), 6.1 (4.6-7.6) and 4.0 (2.9-5.1), respectively. In men aged 60-69 years the incidences were 16.0 (10.7-21.3), 45.6 (27.7-63.4), 19.3 (9.2-35.3) and 8.9 (2.8-20.6), respectively. The incidences of elective AAA surgery in men aged 60-69 years were 22.9 (16.5-29.2), 34.6 (19.1-50.2), 9.7 (1.2-18.5) and 44.2 (27.0-61.6), respectively. CONCLUSIONS: A decrease in incidence of rAAA in men was evident before the implementation of screening. We were yet not able to demonstrate a certain reduction in rAAA incidence after the start of screening.